História e memórias de vida professoral: Maria do Carmo de Miranda nas configurações do magistério - Barbosa, Maria das Graças da Cruz (2014)
The present research purposes to reveal the Maria do Carmo de Miranda s teacher life, reflecting about the teacher exercise and the teacher practices in her relationships with de local government power, during 1960 to 1988 time snip, her pedagogical period of actuation and degree. Then, we discussed her teacher path moments, articulating with the process context, in a relationship between the private and the social political. Using the New Cultural History tenets as foundation, we found in the memory, in the bio-graphical approach and in the Oral History the theoretical methodological way. In front of the written sources absence , oral sources were our primary source and the evidence paradigm helped in the hunt for the traces and leads of the Maria do Carmo de Miran-da s teacher path. In this manner, the teacher Maria do Carmo de Miranda s ex-student(s), ex-teammate(s), family memories, gotten by the oral report guided by semi-structured interviews and the profiled dialogues with the studies of Reis (2000), Burke (1992), Thompson (1992), Bom Meihy (1996, 2005, 2007), Le Goff (2012), Nóvoa (1991; 2007), Dosse (2009), Loriga (2011), Delory-Momberger (2008); Esquisani e Werle (2010), Souza, Passegi, Abrahão (2008), Germano (1994), Saviani (2008) and others were contempladed. According with Nóvoa (2007) studies, researches about teachers life story are inserted as elucidate instrument to the Education History, when permit the reflection about educational aspects, starting by the individual path in a rela-tionship between the private and the social political. The research about the Maria do Carmo de Miranda s teacher life path revealed a professorship configured by the teach-ing feminization residues, involved by the plots and artifices of the partisan political power marking in Paraíba during the investigated period